Album Graphico de Matto-Grosso (1914): história e memória - Câmara, Ana Paula de Oliveira Lopes (2017)
This thesis has as its objective the 1914 Album Gráfico de Matto Grosso ( Graphic Album of Matto Grosso) and the dense process involved in its production, circulation, reprintings and uses. For the research to be initiated it was necessary to access the Policy of Advertisement in Brazil, which started being worked on in the Imperial times with Brazil participating in International expositions, and received a more coherent format on the Republic times with the creation of the Serviço de Propaganda do Brasil (Advertisement Service of Brazil) in 1907. It was in the context of producing advertisement that we can find incentive and production of printings, among them the Álbuns. This luxurious typographical product in fashion in the end of the IX and beginning of the XX centuries, was characterised by the intense use of photographies which present marks of the modernisation process in the cities and information about the potentiality of the States as strategies to incentivate the entrance of immigrants and capital. In order to situate the object of the thesis, the Album Graphico do MattoGrosso in the group of other similar albums, a collection of 17 albums from the Amazonas and Pará States and from the Acre territory was used. These States also lived through economic euphoria when facing possibilities of exporting forest products, enhancing the rubber material. This collection of the States Albums was here denominated as Rede de Album do Brasil Sertao ( Brazil Hinterland Albums Net). It's objective was to change the stigma of these States being the dwelling places of barbáries and unmanageable natural spaces, spreading this new concept to faraway locations. It was in the Policy of Advertisement and in the Album Net contexts that this thesis was contextualised for the further development of questions in reference to their creation, production, reprinting and uses processes